DNA barcoding of sea turtles (Dermochelyidae and Cheloniidae) and its protocol using different tissues quality: implication to conservation managers. (May 2019) - Madduppa, H H; Bahri, S; Subhan, B; Anggraini, N P; Ohoiulun, H; Abdillah, T; Arafat, D; Santoso, P; Sangadji, I M
Abstract: Conservation effort of sea turtles faces several challenges, e.g. habitat destruction, eggs and turtle meat consumptions, or production of souvenirs (e.g. turtle bodies). In their duties, conservation officers may find sea turtles in different condition (e.g. body fragments, eggs, pieces of meat, etc.), usually it is difficult to identify due to incomplete morphology. Therefore, the use of DNA barcoding becomes an alternative for for identification at species level, contribute taxonomic and biodiversity research. This study was conducted to develop a protocol suitable for identifying sea turtles from different tissue samples conditions using DNA barcoding. A total of 16 tissue samples in different condition (fresh, dead-body, smoked-meat) were collected. A protocol was developed to enable identification of tissue samples of different quality or condition. A 719 bp control region fragment was analyzed. The high percentage similarity was confirmed in GenBank CO1 sequence with 99%-100%. Four sea turtle species were identified among the samples, i.e. Chelonia mydas (4 samples), Lepidochelys olivacea (9 samples), Eretmochelys imbricata (2 samples) and Dermochelys coriacea (1 samples). This study was successfully amplified by using DNA target of control region and therefore, will be beneficial for conservation management of sea turtles in Indonesia.